Peer Relationships and Depressive Symptoms Among Adolescents: Results From the German BELLA Study - Adedeji, Adekunle; Otto, Christiane; Kaman, Anne; Reiss, Franziska; Devine, Janine; Ravens-Sieberer, Ulrike (Frontiers in Psychology, 2022)
Background: Poor mental health affects adolescent development and is associated with health and social outcomes in later life. The current study uses cross-sectional data to explore the understudied aspects of peer relationships as a predictor of depressive symptom severity of adolescents in Germany. Method: Data from the German BELLA study were analysed. We focused on the most recent measurement point of the BELLA study and analysed data of 446 adolescents (aged 14-17 years). Peer relationship was measured using four items from the internationally established Patient-Reported Outcome Measurement Information System (PROMIS). Depressive symptoms were assessed via seven items of the German version of the Centre for Epidemiological Studies Short Depression Scale (CES-D). Hierarchical linear regression models were computed to explore the association between depressive symptoms and peer relationships. Hierarchical linear regression models served to determine the added predictive effects of each aspect of peer relationships. Result: The regression model showed that 22% of the variance of the severity of depressive symptoms could be explained by the quality of adolescents' peer relationships (F (1,444) =125.65, p<0.001). Peer acceptance has the most substantial unique contribution to peer relationship as a predictor of depressive symptom severity (Change in R² = .05; Change in F = 27.01, p<0.001). The gender-specific analysis shows different trends for boys and girls. Conclusion: The quality of peer relationships is a significant predictor of adolescents' depressive symptoms severity. Improved peer acceptance, dependability, and ease of making new friends are significantly associated with reduced depression symptoms for Germany's adolescent population.